Reimagining Postgraduate Supervision: Fostering Inclusivity and Support for Students at-risk in Open and Distance Learning Environments - Manase, Ndakaitei; Ngubane, Sindile (Research in Social Sciences and Technology, 2024)
This qualitative study involves six lecturers who have supervised students with disabilities. Participants were purposively selected and interviewed telephonically using semi-structured interviews. The study adopted a thematic data analysis approach to identify patterns in supervision experiences. The paper problematises a deficit approach that is dominantly adopted to identify and design programmes and manage students-at-risk. The analysis of the supervision of postgraduate students-at-risk is framed within the Humanising pedagogy which advances the accommodation of students’ unique needs to develop their capacities for success. This theoretical framework is not adopted much in the open and distance learning context at postgraduate level and the use of supervisors’ insights adds new knowledge to the field that is dominated by students’ experiences. The study established that students do not communicate their disabilities to supervisors timely for early intervention, supervisors are responsive to students’ challenges which include difficulties in academic writing and limited access to research resources and technologies, and supervisors experience systemic challenges in acquiring assistive technology for students with disabilities. This study proposes a humanised supervision model that advances disability inclusivity.